(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
Economic development occupied a great importance, and it became a major goal for most countries, whether they were developed or underdeveloped, especially after the Second World War, when most countries gained their political independence, and Syria, like other countries, sought to achieve its economic development, but it was suffering from a fundamental problem, which is the weakness of its savings. local, forcing it to resort to external sources of financing despite the burdens it poses (political, economic, and social). As a result of the war that Syria has been subjected to since 2011, its economic and service sectors have been subjected to great destruction, which made it necessary to develop plans and strategies for reconstruction, not only to restore what was destroyed by the war and return the economy to before the war, but also in order to develop and advance the economic sectors to keep pace with the process of development. Arabic and international